2017
DOI: 10.1080/24740527.2017.1337467
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of chronic pain content at three undergraduate medical schools in Ontario

Abstract: Background: It has been well documented that interdisciplinary, comprehensive pain education can foster positive pain beliefs among medical students, in addition to improving students' abilities to diagnose and treat pain. Though some work has been done to quantify the number of hours of pain education students receive, the content itself has received little attention. Aims: This study seeks to identify what medical students learn about chronic pain throughout an undergraduate medical degree program in Ontario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In medicine, despite gradual advances in undergraduate pain education, the investigation of undergraduate medical programmes in Canada has highlighted that some continue to lack structure in delivering proper integrated, interdisciplinary content. 13,42 These findings are corroborated internationally in the APPEAL study, a Europe-wide review of pain education for undergraduate health care professionals evaluating curricula from 242 medical schools. 1,9 It was found that 69% of medical schools across Europe have no dedicated pain teaching, with notable inconsistencies in content and a lack of practical teaching methods in pain management—only 26% of courses used placement-based teaching.…”
Section: A Need For Professional Education In Paediatric Pain Acromentioning
confidence: 70%
“…In medicine, despite gradual advances in undergraduate pain education, the investigation of undergraduate medical programmes in Canada has highlighted that some continue to lack structure in delivering proper integrated, interdisciplinary content. 13,42 These findings are corroborated internationally in the APPEAL study, a Europe-wide review of pain education for undergraduate health care professionals evaluating curricula from 242 medical schools. 1,9 It was found that 69% of medical schools across Europe have no dedicated pain teaching, with notable inconsistencies in content and a lack of practical teaching methods in pain management—only 26% of courses used placement-based teaching.…”
Section: A Need For Professional Education In Paediatric Pain Acromentioning
confidence: 70%
“…The oil present in the diets was extracted following the procedure described by Bligh & Dyer [28]. Samples were esterified according to a previously described procedure [29].…”
Section: Fatty Acids Compositionmentioning
confidence: 99%
“…A number of studies demonstrate success in teaching on the topic of chronic non-cancer pain. Teaching interventions tended to include a foundation of knowledge such as teaching on pain mechanisms, pharmacology, and pain management [37,38]. Such theory-driven interventions led to improved scores on assessment [39].…”
Section: Knowledge (Cognitive)mentioning
confidence: 99%
“…Methods of teaching should be considered in the explicitly taught curriculum. Authors recommended an integrated approach [40,41] and one which drew on the skills and knowledge from a variety of disciplines [37,42]. Curriculum mapping was recommended by Howman et al [33] in order to identify ways in which this integration could be implemented.…”
Section: Knowledge (Cognitive)mentioning
confidence: 99%